(3GdYbGQ GdCedGc GdYehejI hCedGc GdOhdI (B/s - (3MLQj, aDGO s; (3Hf HdI , CMeO s ((3GdLRGFQ (B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2006)
(3jYJHQ gPG GdcJGH LRA ef SdSdI GdbhGfjf GdEOGQjI jMed eLehYI ef GdbhGfjf GdNGUI HGdYbGQGJ hGdCedGc GdYehejI hCedGc GdOhdI s
Keywords: (3GdYbGQGJs; (3GdedcjI GdYbGQjIs